Here's the question you clicked on:
mahmit2012
solve the problem without calculate x
|dw:1336859839299:dw|
root n=1-n square both sides n=(1-n)^2 then solve
|dw:1336860022459:dw| |dw:1336860159440:dw|
please dont calculate x or n...
one is extraneous :o^^
just calculate 2x+xsqx
oh are these 2 equations linked with each other, like is the value of n for the first equation = n for second? ;o
from 1st eqn\[x = 1 - \sqrt{x}\] replacing 'x' with this value in \[x \sqrt{x}\] we get\[2x + (1 - \sqrt{x})\sqrt{x}\]\[2x + (\sqrt{x} - x)\]\[x + \sqrt{x} = 1, as per eqn 1.\]
plug in value of n from first equation then plug it into second
i know but that is wrong way please shashi solution
Don't know if it works... \[x+\sqrt x =1\] \[2x +x\sqrt x\]\[ = 2(1-\sqrt x) + x\sqrt x\]\[ = 2-2\sqrt x + x\sqrt x\]\[ = 2 - \sqrt x( 2- x)\]\[ = 2 - \sqrt x( 2 - (1-\sqrt x))\]\[ = 2 - \sqrt x( 1 +\sqrt x)\]\[ = 2 - \sqrt x - x\]\[=2 - (\sqrt x + x)\]\[=2-1\]\[=1\] Seems I've done something wrong :|